TBL Integration on Determining Supplier Selection Criteria in Bottled Water Company - Nala, Aditya Asmara; Harianto, Harianto; Nurhayati, Popong (International Journal Labs, 2023)
Business sustainability has become the company ambition to ensure their business existence in the long term. Companies are competing to adopt sustainability objectives in every aspect of their operations. In the context of sustainability, the term triple bottom line (TBL) is widely known as an integration of economic perspectives, environmental perspectives, and social perspectives that underlie business operations. PT ABC is a bottled water company that adopt sustainability objective since the supplier selection process. It aims to ensure that only the right suppliers which deserve to enter the company's business ecosystem. Unfortunately, supplier selection criteria at PT ABC currently only focus on economic perspective. Environmental and social perspective have not yet significantly influenced supplier selection decisions. Therefore, this study aims to determine supplier selection criteria in PT ABC based on integration of economic, environmental, and social perspective. Integration of these three perspectives is important to strengthen supplier selection decisions alignment with business sustainability objectives. Researchers reviewed 100 scientific journals which discussed supplier selection criteria from 2012 to 2023. As a result, researchers set 13 selection criteria and 20 indicators that can be used to select suppliers at PT ABC.